DESAIN KEMASAN RAMAH LINGKUNGAN DARI LIMBAH KARDUS DENGAN METODE DESIGN DRIVEN MATERIAL INNOVATION - Devanny Gumulya (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2022)
Businesses' strategies have shifted to more eco-friendly and sustainable paths as customer expectations toward eco-friendly products continue to progress. Many industries have preferred sustainable packaging in recent years. Because paper waste is abundant around us, recycling it will be very beneficial to the environment. The goal of this research is to look into how to recycle paper waste using design driven material innovation (DDMI) methods. The study employs a qualitative, research-through-design approach, in which researchers conduct research by developing a design project. The research findings are prototypes of snack packaging designs made from recycled paper using the DDIM method. Furthermore, the study's findings indicate that several factors are important to DDIM: knowledge of production technology, knowledge of market trends, and knowledge integration. The study adds to the body of knowledge in product design by instructing product designers on how to create new innovative DIY materials using the DDMI method.packaging design, diy material, material innovation